Genetic and Clinical Analysis of ABCA4‐Associated Disease in African American Patients. Issue 10 (October 2014) - Zernant, Jana; Collison, Frederick T.; Lee, Winston; Fishman, Gerald A.; Noupuu, Kalev; Yuan, Bo; Cai, Carolyn; Lupski, James R.; Yannuzzi, Lawrence A.; Tsang, Stephen H.; Allikmets, Rando
ABSTRACT Autosomal recessive Stargardt disease (STGD1) is caused by hundreds of mutations in the ABCA4 gene, which are often specific to racial and ethnic groups. Here, we investigated the ABCA4 variation and their phenotypic expression in a cohort of 44 patients of African American descent, a previously under‐characterized racial group. Patients were screened for mutations in ABCA4 by next‐generation sequencing and array‐comparative genomic hybridization (aCGH), followed by analyses for pathogenicity by in silico programs. Thorough ophthalmic examination was performed on all patients. At least two (expected) disease‐causing alleles in the ABCA4 gene were identified in 27 (61.4%) patients, one allele in 11 (25%) patients, and no ABCA4 mutations were found in six (13.6%) patients. Altogether, 39 different disease‐causing ABCA4 variants, including seven new, were identified on 65 (74%) chromosomes, most of which were unique for this racial group. The most frequent ABCA4 mutation in this cohort was c.6320G>A (p.(R2107H)), representing 19.3% of all disease‐associated alleles. No large copy number variants were identified in any patient. Most patients reported later onset of symptoms. In summary, the ABCA4 mutation spectrum in patients of West African descent differs significantly from that in patients of European descent, resulting in a later onset and "milder" disease.